2018
DOI: 10.1002/anie.201711688
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Bridged Ionic Liquid Polymer on a Carbon Nanotube for Enhanced Oxygen Evolution Reaction Activity

Abstract: By taking inspiration from the catalytic properties of single‐site catalysts and the enhancement of performance through ionic liquids on metal catalysts, we exploited a scalable way to place single cobalt ions on a carbon‐nanotube surface bridged by polymerized ionic liquid. Single dispersed cobalt ions coordinated by ionic liquid are used as heterogeneous catalysts for the oxygen evolution reaction (OER). Performance data reveals high activity and stable operation without chemical instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…The composites were tested as excellent catalysts for the oxygen evolution reaction (OER) because of the variations in the electronic structure of Co by coordinating with PIL, as well as the excellent conductivity contributed by CNTs. 105 The synergistic effect between PIL and CNTs was clearly illustrated in a report by using redox-active catechol-bearing PIL-CNT composites as high-performance lithium-ion battery cathodes. The composite delivered a high reversible capacity of 247 mA h g À1 at 0.2C with a capacity of 134 mA h g À1 at 60C and retained 86% of its initial capacity during the prolonged 5000 cycling tests in comparison to a neutral polymer PAmcat in control experiments (Fig.…”
Section: Pil-carbon Compositesmentioning
confidence: 97%
“…The composites were tested as excellent catalysts for the oxygen evolution reaction (OER) because of the variations in the electronic structure of Co by coordinating with PIL, as well as the excellent conductivity contributed by CNTs. 105 The synergistic effect between PIL and CNTs was clearly illustrated in a report by using redox-active catechol-bearing PIL-CNT composites as high-performance lithium-ion battery cathodes. The composite delivered a high reversible capacity of 247 mA h g À1 at 0.2C with a capacity of 134 mA h g À1 at 60C and retained 86% of its initial capacity during the prolonged 5000 cycling tests in comparison to a neutral polymer PAmcat in control experiments (Fig.…”
Section: Pil-carbon Compositesmentioning
confidence: 97%
“…Wurster et al found that the OER activity was nonlinearly dependent on the coordination positions of Fe and Co in a supramolecular structure. Ding et al developed a sandwich structure where CNT was coated with a uniform layer of polymerized ionic liquids (PIL), and Co atoms were dispersed at the interface. The resulting Co‐PIL‐CNT SACs showed much better OER catalytic activity than Co 3 O 4 /CNT and CoCO 3 despite a much lower Co content.…”
Section: Electrocatalytic Performancementioning
confidence: 99%
“…In recent years, SACs have also found significant applications in electrochemical energy conversion and storage, in particular, ORR, OER, HER, and CO 2 RR, and the results suggest that the supporting substrates such as carbon‐based materials not only provide anchoring sites for the single metal atoms, offer good electrical conductance with the graphitic skeletons, but also manipulate the charge density and electronic structure of the metal atoms because of strong interfacial interactions between the metal atoms and adjacent carbon atoms. Such attributes may be exploited for the enhancement of the electrocatalytic performance due to generation of an increasing number of active sites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as a potential electrocatalyst with high activity for OER, the stability is also an important property to ensure that the catalyst can release a high activity for a long time (Ding et al, 2018). As shown in the inset curve of Figure 6B, chronoamperometry was conducted at an overpotential of 310 mV for CoP-CGP2.…”
Section: Electrochemical Testsmentioning
confidence: 99%